Scaling Up Access to Electricity : Emerging Best Practices for Mini-Grid Regulation - Greacen, Chris (World Bank, Washington, DC, 2015)
This brief will focus on enabling regulations for mini-grids, providing an overview of key issues, options, and good practices. While appropriate regulations are not all that is needed to spur mini-grid development, is usually one of the first obstacles that potential developers face and therefore the most urgent issue for governments. The authors draw on a case study of Tanzania, a pioneer in setting an enabling and light-handed regulatory framework for mini-grids. Given the urgency of leveraging private sector investments for reaching the universal access targets of the international sustainable energy for all projects, the authors also focus on regulatory issues relevant to private sector entrepreneurs and investors. Mini-grid entrepreneurs need to know that their investment of time and money will have a reasonable chance not just of being repaid but also of returning a profit. A clear and credible regulatory framework that makes and enforces fair and efficient decisions in a timely manner helps entrepreneurs make informed investment decisions. The key characteristics of such a framework, described include licensing and registration, tariff setting, and what happens when the main grid reaches the mini-grid.